B-Factor Rescaling for Protein Crystal Structure Analyses - Georg Mlynek; Kristina Djinović-Carugo; Oliviero Carugo (Crystals, 2024)
The B-factor, also known as the atomic displacement parameter, is a fundamental metric in crystallography for quantifying the positional flexibility of atoms within crystal lattices. In structural biology, various developments have expanded the use of B-factors beyond conventional crystallographic analysis, allowing for a deeper understanding of protein flexibility, enzyme manipulation, and an improved understanding of molecular dynamics. However, the interpretation of B-factors is complicated by their sensitivity to various experimental and computational factors, necessitating rigorous rescaling methods to ensure meaningful comparisons across different structures. This article provides an in-depth description of rescaling approaches used for B-factors. It includes an examination of several methods for managing conformational disorder and selecting the atom types required for the analysis.